2018
DOI: 10.1016/j.jcpa.2018.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Urocystitis and Ureteritis in Holstein Calves with Septicaemia Caused by Salmonella enterica Serotype Dublin

Abstract: Salmonellosis is an enteric or multisystemic disease of global distribution that affects numerous animal species. Although Salmonella enterica has been associated with urinary tract lesions in man, information on urocystitis/ ureteritis in cattle caused by salmonellae is lacking. This communication describes lesions of the inferior urinary tract in four Holstein calves with septicaemia caused by S. enterica subsp. enterica serotype Dublin. Examination of the urinary bladder revealed either diffuse irregular th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 8 publications
(19 reference statements)
3
10
0
Order By: Relevance
“…Cattle from one to three months of age were the most frequently affected, accounting for 80% of all cases. Similar data were observed in cattle from other regions of Brazil (Marques et al 2013), Uruguay (Costa et al 2018) and the United States (Pecoraro et al 2017). Documentation of salmonellosis is more common in dairy cattle (Radostits et al 2007); however, in the present study, it was observed in both dairy and beef calves.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Cattle from one to three months of age were the most frequently affected, accounting for 80% of all cases. Similar data were observed in cattle from other regions of Brazil (Marques et al 2013), Uruguay (Costa et al 2018) and the United States (Pecoraro et al 2017). Documentation of salmonellosis is more common in dairy cattle (Radostits et al 2007); however, in the present study, it was observed in both dairy and beef calves.…”
Section: Discussionsupporting
confidence: 86%
“…This nonproper submission of material for diagnosis is not restricted to cases of salmonellosis and is frequently observed in many veterinary diagnostic laboratories (Lucena et al 2010, Souza et al 2015. The use of IHC for the diagnosis of salmonellosis is described in sheep (Dagleish et al 2010), horses (Juffo et al 2017), swine (Watanabe et al 2011), turkeys (Beyaz et al 2010) and cattle (Pecoraro et al 2017, Costa et al 2018. In all analyzed materials in the present study, there was positive immunoreactivity in the liver and lung.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The necrosis and slough of the tail tips and ear that were observed in some calves of this report are chronic changes of septicemic salmonellosis, possibly resulting from immunomediated host reactions [9]. The necropsy and histopathological findings were similar to those observed in outbreaks previously described [1,10,11,13].…”
Section: Discussionsupporting
confidence: 84%
“…The diagnosis of septicemic salmonellosis was based on clinical and pathological findings and confirmed through microbiological culture and identification of S. Dublin by the PCR technique. The diagnosis followed the criteria recommended by others [9][10][11].…”
Section: Discussionmentioning
confidence: 99%